2013
DOI: 10.1371/journal.ppat.1003852
|View full text |Cite
|
Sign up to set email alerts
|

The CD8-Derived Chemokine XCL1/Lymphotactin Is a Conformation-Dependent, Broad-Spectrum Inhibitor of HIV-1

Abstract: CD8+ T cells play a key role in the in vivo control of HIV-1 replication via their cytolytic activity as well as their ability to secrete non-lytic soluble suppressive factors. Although the chemokines that naturally bind CCR5 (CCL3/MIP-1α, CCL4/MIP- 1β, CCL5/RANTES) are major components of the CD8-derived anti-HIV activity, evidence indicates the existence of additional, still undefined, CD8-derived HIV-suppressive factors. Here, we report the characterization of a novel anti-HIV chemokine, XCL1/lymphotactin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 50 publications
(52 reference statements)
3
49
0
Order By: Relevance
“…These data are consistent with findings published after our experiments were performed, showing that an alternative all-␤ conformation of XCL1 forms a dimer, binds glycosaminoglycans, and suppresses HIV replication via blockade of attachment and entry into cells and that this form of the protein lacks chemotactic activity (35). The protein supplied by R&D Systems is tested to demonstrate chemotactic activity, so we conclude that the version of XCL1 used in our experiments was in the classic XCL1 conformation and would not be expected to suppress HIV replication.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are consistent with findings published after our experiments were performed, showing that an alternative all-␤ conformation of XCL1 forms a dimer, binds glycosaminoglycans, and suppresses HIV replication via blockade of attachment and entry into cells and that this form of the protein lacks chemotactic activity (35). The protein supplied by R&D Systems is tested to demonstrate chemotactic activity, so we conclude that the version of XCL1 used in our experiments was in the classic XCL1 conformation and would not be expected to suppress HIV replication.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, soluble epidermal growth factor receptor (sEGFR) was also uniquely elevated in ECs compared to levels in the NEG group but was not studied further due to lack of available reagents. Of the five cytokines selected for further in vitro study, CCL14 (32), SDF-1 (33,34), and XCL1 (35) have been previously associated with control of HIV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Using XCL1 variants stabilized in each of the two alternative conformations, we found that inhibition of HIV-1 requires access to the GAG-binding, alternative conformation, while the XCR1-binding (classic, chemokine-like) fold lacks anti-viral function. However, by enzymatic removal of GAGs on HIV-1 target cells, we demonstrated that interaction with cell surface GAGs is not required for the antiviral activity of XCL1, in agreement with the evidence that HIV-1 inhibition is mediated by direct interaction of the chemokine with gp120 (2). Altogether, these observations point to a role of electrostatic interactions, potentially related to those involved in GAG binding, in XCL1 interaction with gp120 (6)(7)(8).…”
supporting
confidence: 87%
“…To investigate the relationship between the antiviral and GAG-binding activities of XCL1, we generated a panel of mutants bearing individual alanine substitution of all basic amino acids in the structured core of XCL1 (amino acids 1 to 54), as well as three residues within the C-terminal tail (12). Since mutation of some basic residues was previously shown to shift the conformational equilibrium of XCL1 toward the monomeric chemokine conformation (13), which lacks HIV-inhibitory activity (2), mutagenesis was performed on the stabilized XCL1 variant W55D, in order to ensure that the functional impact of each substitution could be interpreted in the context of the all-␤ dimeric structure (2). All of the mutants were tested for antiviral activity against a reference CCR5-tropic (R5) HIV-1 isolate (BaL) in susceptible target cells (TZM-bl).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation